Intelligent Sensorless and Rotor Flux Linkage Control Design of PMSM Servo Drive - Radhika, S.; Beno, Marsalin; Jaikumar, R. A. (Asian Journal of Electrical Sciences, 2015)
The permanent-magnet synchronous motors (PMSM) are widely used in industrial servo applications due to its high power density. However, there exists a risk of potential irreversible demagnetization in the rotor magnets due to high temperature rise or large demagnetizing current. Since the rotor permanent magnet (PM) flux linkage decreases as the PM temperature increases, it is desirable to estimate the rotor flux linkage value since the decrease in rotor flux linkage in turn reduces the performance of the drive. Sensor less control method is also involved to improve the performance of machine. The proposed method consists of a thermocouple and an adaline estimator which estimates the temperature of the machine and distortion in the voltage respectively. The thermocouple is placed on either sides of the stator. By continuously monitoring or tracking the rotor flux linkage and compensating the VSI nonlinearity the performance of the PMSM can be improved. Hence the machine can possess high efficiency.